Bilateral agreement for the academic year 2011-2015 Lifelong Learning Programme (LLP): Higher Education Erasmus between Universidad Rey Juan Carlos and Universidade Lusíada de Lisboa - Universidade Lusíada de Lisboa (2016)
- Cooperate in the LLP/Erasmus activities - Subject area: International relations; Architecture; Tourism; Law.